2022
DOI: 10.3390/foods11131928
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Approach to Enhance the Safety of Ready-to-Eat Rice and Extend the Refrigerated Preservation

Abstract: Rice is a broad-spectrum meal consumed annually in large amounts. Ready-to-eat rice is a member of dishes with a high risk of contamination. The present study aimed to increase the safety and shelflife of ready-to-eat rice during temporary storage. To prepare a mixture for extraction, three spices were chosen ginger: thyme:coriander (1:2:1). Two types of extract were prepared, aromatic and water extracts. The bioactive aromatic extract was preserved by encapsulation using chitosan nanoparticle preparation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…These results are similar to those of He et al [36], who reported that chlorogenic, caffeic, and ferulic acid in citrus peels ranged from 8.8 to18.7, 4.5 to 29.9, and 14.4 to 97.8 μg/g, respectively, as well as, lemon peel contained higher amounts of ferulic, p-coumaric and caffeic acids (44.9, 34.9 and 14.2 mg/100 g, respectively) [37]. Otherwise, these results are similar to those of Albaridi et al [38], who said that the phenolic acids contents of the water extract of ginger:thyme: coriander mixture using HPLC were chlorogenic, ferulic acids, coumarin, and salicylic acid) (48.63, 225.71, 31.5, and 907.16 mg/100g, respectively). As shown in Table 1, the concentration of phenolic compounds was significantly greater in ethanol extracts than in aqueous extracts; this difference can be attributed to the greater polarity of ethanol, which increases extraction capabilities, yielding more phytochemicals and active constituents from the basic materials [39].…”
Section: Fractionation Of Phenolic Compounds Of Lemon and Ginger Peel...supporting
confidence: 87%
“…These results are similar to those of He et al [36], who reported that chlorogenic, caffeic, and ferulic acid in citrus peels ranged from 8.8 to18.7, 4.5 to 29.9, and 14.4 to 97.8 μg/g, respectively, as well as, lemon peel contained higher amounts of ferulic, p-coumaric and caffeic acids (44.9, 34.9 and 14.2 mg/100 g, respectively) [37]. Otherwise, these results are similar to those of Albaridi et al [38], who said that the phenolic acids contents of the water extract of ginger:thyme: coriander mixture using HPLC were chlorogenic, ferulic acids, coumarin, and salicylic acid) (48.63, 225.71, 31.5, and 907.16 mg/100g, respectively). As shown in Table 1, the concentration of phenolic compounds was significantly greater in ethanol extracts than in aqueous extracts; this difference can be attributed to the greater polarity of ethanol, which increases extraction capabilities, yielding more phytochemicals and active constituents from the basic materials [39].…”
Section: Fractionation Of Phenolic Compounds Of Lemon and Ginger Peel...supporting
confidence: 87%
“…While, 80% acetone recommended for total phenolic compounds from turmeric, torch ginger and lemon grass compared to 80% acetone, 80% ethanol. Also, water can be extract phenolic compounds (WHANGSOMNUEK et al, 2018;ALBARIDI et al,2022). From the previous results it can be observed that vinegar and ethanol as a solvent were more efficient than water as a solvent to increase the efficiency of extracting the active compounds from the natural materials responsible for rooting.…”
Section: Discussionmentioning
confidence: 99%
“…From the previous results it can be observed that vinegar and ethanol as a solvent were more efficient than water as a solvent to increase the efficiency of extracting the active compounds from the natural materials responsible for rooting. Ethanol more use in extracting chemical compounds and solvent for many chemical compounds such as phenols (WHANGSOMNUEK et al, 2018); ALBARIDI et al, 2022) and sugars (DUBOIS et al, 1956).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations